2015
DOI: 10.1083/jcb.201508072
|View full text |Cite
|
Sign up to set email alerts
|

Whole-proteome genetic analysis of dependencies in assembly of a vertebrate kinetochore

Abstract: Whole-proteome analysis of isolated mitotic chromosomes from 11 kinetochore structural and assembly mutants is used to develop dependency and correlation maps for protein subcomplexes that confirm many published interactions and also reveal novel dependencies between kinetochore components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 82 publications
7
43
1
Order By: Relevance
“…Studies in Saccharomyces cerevisiae report a role for the COMA complex (CENP-O/-P/-Q/-R/-U complex homolog) in the looping of centromere chromatin (45). However, our results plus other recent studies have failed to identify a function for this complex in vertebrate kinetochores (37,41).…”
Section: The Role Of Ccan Proteins In the Maintenance Of Kinetochorecontrasting
confidence: 55%
See 1 more Smart Citation
“…Studies in Saccharomyces cerevisiae report a role for the COMA complex (CENP-O/-P/-Q/-R/-U complex homolog) in the looping of centromere chromatin (45). However, our results plus other recent studies have failed to identify a function for this complex in vertebrate kinetochores (37,41).…”
Section: The Role Of Ccan Proteins In the Maintenance Of Kinetochorecontrasting
confidence: 55%
“…Indeed, CENP-C is required to efficiently recruit both inner and outer kinetochore components during kinetochore assembly (34)(35)(36)(37).…”
Section: The Role Of Ccan Proteins In the Maintenance Of Kinetochorementioning
confidence: 99%
“…The CENP-S/-X centromere complex, reported to form a heterotetramer with CENP-T/-W (Nishino et al 2012), was not identified as a CENP-W-GFP interactor by our MS analysis. This is consistent with recent reports that predict that CENP-T/-W and CENP-S/-X are part of separate protein cohorts within the kinetochore (Samejima et al 2015). In agreement with previous reports regarding CENP-T/-W interactions, we did not find CenH3 CENP-A in our CENP-W-GFP pull-downs (Hori et al 2008;Abendroth et al 2015), confirming the specificity of our approach.…”
Section: Fact Subunits Interact With the Cenp-t/-w Complexsupporting
confidence: 82%
“…CENP-A is extremely stable at centromeres53, thus making it hard to observe large effects. Our detailed proteomic analysis of isolated mitotic chromosomes showed only moderate differences in CENP-A levels even when critical assembly factors such as HJURP or Mis18α were depleted for several days54. Kinetochores depleted of H3K4me2 remained functional for several days until CENP-A levels fell by >50%.…”
Section: Discussionmentioning
confidence: 73%